The Image of a Hero in Western and Russian Social Advertising - A. G. Zhukova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to a comparative study of the image of a hero / superhero in Russian and Western social advertising. The relevance of the study is determined by the contrast of globalization processes, on the one hand, and the desire to preserve nationally oriented values, on the other. The novelty of the study lies in comparing the ideological and linguocultural representations of the image of the hero / superhero, reflected in the socio-advertising text. The results of the study are based on a contextual analysis of the geroy and hero tokens, supergeroy and superhero , as well as non-verbal symbols associated with these concepts presented in the structure of creolized advertising text. In the structure of the image of the hero / superhero, both semantic components (for example, a military metaphor) and specific representations that are determined by the cultural code and ideological identifications, are revealed that are common for Russian and Western social advertising. It is proved that those components of the hero’s image that are connected with the axiology of culture (“peaceful heroism” interpreted as socially approved behavior in general) are more likely to have positive connotations than those that are due to ideological ideas. It is concluded that the image of a superhero in Russian linguistic culture, on the one hand, is understandable and even already familiar, on the other hand, it is rejected as a representative of an alien culture and ideology.